Physical Drivers of Phytoplankton Bloom Initiation in the Southern Ocean's Scotia Sea. Issue 8 (15th August 2019) - Prend, Channing J.; Gille, Sarah T.; Talley, Lynne D.; Mitchell, B. Greg; Rosso, Isabella; Mazloff, Matthew R.
Abstract: The Scotia Sea is the site of one of the largest spring phytoplankton blooms in the Southern Ocean. Past studies suggest that shelf‐iron inputs are responsible for the high productivity in this region, but the physical mechanisms that initiate and sustain the bloom are not well understood. Analysis of profiling float data from 2002 to 2017 shows that the Scotia Sea has an unusually shallow mixed‐layer depth during the transition from winter to spring, allowing the region to support a bloom earlier in the season than elsewhere in the Antarctic Circumpolar Current. We compare these results to the mixed‐layer depth in the 1/6° data‐assimilating Southern Ocean State Estimate and then use the model output to assess the physical balances governing mixed‐layer variability in the region. Results indicate the importance of lateral advection of Weddell Sea surface waters in setting the stratification. A Lagrangian particle release experiment run backward in time suggests that Weddell outflow constitutes 10% of the waters in the upper 200 m of the water column in the bloom region. This dense Weddell water subducts below the surface waters in the Scotia Sea, establishing a sharp subsurface density contrast that cannot be overcome by wintertime convection. Profiling float trajectories are consistent with the formation of Taylor columns over the region's complex bathymetry, which may also contribute to the unique stratification. Furthermore, biogeochemical measurements from 2016 and 2017 bloom events suggest that vertical exchange associated with this Taylor column enhances productivity by delivering nutrients to the euphotic zone. Plain Language Summary: Tiny algae called phytoplankton form the base of the marine food web and absorb carbon dioxide from the atmosphere through photosynthesis. Therefore, understanding the processes that control the location and timing of phytoplankton blooms is necessary to accurately model marine ecosystems and the global carbon cycle. In this study, we examine the upper ocean conditions that support the earliest and largest offshore spring phytoplankton bloom in the Southern Ocean, which surrounds Antarctica and is a key region of carbon uptake for the global ocean. Observational data and model output both suggest that the bloom region has unique stratification, which is conducive to bloom development. By releasing virtual particles into a climate model and tracking their position, we find that currents transport cold water to the bloom site from the Weddell Sea. This cold water is key to explaining the region's unusual stratification. Finally, we analyze new observations taken by robotic floats of the 2016 and 2017 blooms. These data suggest that biological productivity is closely linked to the seafloor topography. This is because flow over topography leads to enhanced mixing, which delivers essential nutrients to the sunlit upper ocean where phytoplankton can grow. Key Points: Shallow mixed layers in the Scotia Sea support the earliest and largest offshore spring phytoplankton bloom in the Southern Ocean About 10% of the water in the bloom region is advected from the Weddell Sea, which helps set the unique stratification Vertical transport associated with a stratified Taylor column may enhance productivity by supplying subsurface iron to the euphotic zone